DocStone: A Blockchain-Based Architecture for a Customizable Document Registration Service - Soares, Pamella; Saraiva, Raphael; Fernandes, Iago; Souza, Jerffeson Teixeira; Loiola, Ricardo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2022)
Document management ensures the proper production, storage, and use of documents in many organizations. In this sense, digitization has become a relevant factor for the improvement of processes in several aspects of document management. In this context, blockchain is relevant due to its ability to meet the requirements of any document management solutions. However, there are still difficulties in the efficiency of blockchain infrastructure implementation. On the other hand, existing solutions present proposals for specific contexts and strict business rules. Therefore, this study proposes an architecture designed to provide and facilitate the integration of blockchain-based document registration and verification for use by third-party applications from different domains. Furthermore, this solution allows the configuration of parameters in creating customizable document templates and selecting blockchains. To evaluate the proposed solution, we performed performance tests for different scenarios and blockchains, demonstrating differences between public and private blockchains when performing read and write operations.